The practice of different structural systems in Cypriot architecture from pre-historic to modern times - Ozay, G.; Ozay, N. (Wit Press/Computational Mechanics Publications, 2007)
Cyprus is one of the oldest islands in the Mediterranean Sea, where human settlements can be traced. Over the centuries, it was governed by different states. Under the influence of each cultural milieu various periods were developed in the history of Cyprus. Each period reflects the age and its social life style, economic conditions, technological opportunities, religion and political structure. Today, it is possible to observe lots of architectural examples from the various periods. Some of them have been demolished under the effects of time and physical factors. However, the strong and well-designed structures carried their most important parts to the present. In this study, the structural evolution is investigated under the influence of different architectural periods of Cyprus. It starts with the pre-historic times of the island and continues until the beginning of modem times. Various structural systems and building materials are all discussed bearing in mind the historical development and changing conditions of Cyprus. In other words, the practice of different structural systems in architecture is argued in related to the environment, social requirements and life styles which reflect the influences of the sustainable design.
10th International Conference on Studies, Repairs and Maintenance of Heritage Architecture -- JUL 04-06, 2007 -- Prague, CZECH REPUBLIC
Keywords: Cyprus; architectural periods; building materials; structural systems